Robust Silica–Polyimide Aerogel Blanket for Water-Proof and Flame-Retardant Self-Floating Artificial Island - Liu, Riyong; Wang, Jin; Liao, Jianhe; Zhang, Xuetong (Frontiers in Materials, 2021)
A robust silica–polyimide (PI) aerogel blanket is designed and synthesized using the PI foam as the matrix and silica aerogel as the filler through an in situ method, where sol–gel transition of silica precursor occurs in pores of the PI foam, followed by the hydrophobization and ambient pressure drying. The density of the aerogel blanket ranges from 0.036 to 0.196 g/cm3, and the low density is directly controlled by tailoring the silica concentration. The specific surface area of the aerogel blanket reaches 728 m2/g. These features of the blanket result in a low thermal conductivity of 0.018 W/mK, which shows a remarkable reduction of 59% compared to that of the PI foam (0.044 W/mK). As a result, a remarkable decrease of 138°C is achieved using the silica blanket as the thermal insulator on a hot plate of approximately 250°C. In addition, the temperature degradation of the blanket is around 500°C, and up to 86% of mass remaining at 900°C is obtained. The blanket is resistant at extremely harsh conditions, e.g., 600°C for 30 min and 1,300°C for 1 min, and no open flame is observed, suggesting a significant flame-retardant of the blanket. Owing to the three-dimensional (3D) porous framework of the PI foam, the silica aerogel is encapsulated in the PI foam and the blanket exhibits strong mechanical property. The silica–PI aerogel can be reversibly compressed for 50 cycles without reduction of strain. The contact angle of the blanket is 153°, which shows a superior waterproof property. Combining with the low density, low thermal conductivity, flame-retardant, and strong mechanical strength, the aerogel blanket has the potential as an artificial island, which is safe (waterproof and flame-retardant), lightweight, comfortable, and easy to be moved.